2020
DOI: 10.1002/admi.202001021
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot Enabled Perovskite Thin Film with Enhanced Crystallization, Stability, and Carrier Diffusion via Pulsed Laser Nanoengineering

Abstract: transport dynamics, which is the key for high-performance perovskite devices. At present, precursor solution additive as a convenient and effective method has been widely used in the structural optimization of perovskite films, [8] such as doping in the perovskite lattice to form bonds, [9] and additives to form hydrogen bonds with perovskites. [10] Quantum dots (QDs) are often doped in perovskite grain boundaries to reduce the boundary barrier for promoting the transport of photogenic carriers. [11] In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In this context, it was recently shown that by scanning a pulsed laser over carbon quantum dots implanted into a perovskite thin film, the resulting grain boundaries are much larger than those following standard thermal annealing, yielding enhanced crystallinity and phase stability. [115] Thermal scanning probe lithography and direct laser writing are extremely versatile techniques for patterning nanostructures on different materials. On the other hand, although a lot of effort has been done in order to increase the throughput and minimum feature size of SPL, [116] optical lithography, particularly extreme UV lithography (EUVL), are far from being reached in terms of joint resolution and large scale production when deal-ing with electronic devices.…”
Section: Electronicsmentioning
confidence: 99%
“…In this context, it was recently shown that by scanning a pulsed laser over carbon quantum dots implanted into a perovskite thin film, the resulting grain boundaries are much larger than those following standard thermal annealing, yielding enhanced crystallinity and phase stability. [115] Thermal scanning probe lithography and direct laser writing are extremely versatile techniques for patterning nanostructures on different materials. On the other hand, although a lot of effort has been done in order to increase the throughput and minimum feature size of SPL, [116] optical lithography, particularly extreme UV lithography (EUVL), are far from being reached in terms of joint resolution and large scale production when deal-ing with electronic devices.…”
Section: Electronicsmentioning
confidence: 99%
“…In situ photopatterning CsPbI 3 perovskite NCs was also achieved by using pulsed lasers, such as 405 or 1064 nm nanosecond laser 68,69 and high repetition 800 nm femtosecond laser 70,71 . The PL quantum yield reaches 92% and the obtained minimum line width is 0.9 μm 68 .…”
Section: Photo-processing Of Perovskitesmentioning
confidence: 99%
“…In situ photopatterning CsPbI 3 perovskite NCs was also achieved by using pulsed lasers, such as 405 or 1064 nm nanosecond laser 68,69 and high repetition 800 nm femtosecond laser 70,71 . The PL quantum yield reaches 92% and the obtained minimum line width is 0.9 μm 68 . Compared with the thermal annealing route, nanosecond laser can generate higher compacted perovskite films with larger crystal size (Fig.…”
Section: Photo-processing Of Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic photovoltaics (OPVs), which convert solar energy into electric energy, have broad application prospects due to low cost, good flexibility, and ease of large-area preparation. Benefiting from the development of conjugated molecules and optimization of active layer morphology, the power conversion efficiency (PCE) of state-of-art single-junction OPVs has exceeded 19% for bulk heterojunction (BHJ) structures . However, the performance of OPVs still falls behind that of perovskite- or silicon-based solar cells. Therefore, further improving PCE is the primary aim of OPV research.…”
Section: Introductionmentioning
confidence: 99%